Spontaneous biliodigestive fistulas and their complications - Alba, Enrique (Cirugía del Uruguay, 1972)
Pathological, clínica! and therapeutical aspects of bilio-digestive fistulas are updated through the study of 21 cases treated by the author. Bibliographic dats is revised. The heterogenous situations . in which fistulas are found are analyzed, since they g,nerally constitute a secondary symptom with varied significance within the group of associated lesions. Statistical consideration shows for Uruguay a high percentage of lithiasic et. iology compared with the ulcerous or neoplasic type, thus differing from lower figures in the statistics for other countries. Pathology of fistulas of lithiasic origin stress the fact that it complicates the situation, for the combined nd potentialized action of biliary hypertension and parietal alteration, combined with infection and gallstone pressure determinating factors in the formation of the fistula. The cases studied show that there is no specific symptomatology. Patients are generally in the sixth or seventh decade of their lives, are generally women with cardiovascular alterations, overweight and diabetical. Diagnosis, except in rare cases, is the result of random radiological findings, of a complication (in general gallstone ileus), or, more often, during surgery. Exeept in sone cases when is contraindication by reason of the patient's precarious general condition, treatment consists of surgery. Surgical goals should follow an arder of priori ti es: -Digestive and biliary transit free of obstacles: -Elimination of biliary infection; -Elimination of fistula. and their treatment. Hemorrhage: its massive and cataclysmic character; the need for immediate surgical hemostasis; inclusion of bilio-digestive fistulas in the. diagnosis of massive digestive hemorrhages. Cholangitis: caused or aggravated by backflow. This may be the most difficult problem and may occasionally be insoluble. The paper contains an account of treatment for reversible _cases. Gallstome ileus: it accounted for 9 out of 16 cases of bilio-enteric fistulas. Its polimorphic symptomatology and digestive and humoral complications are analyzed. Criteria for its surgical treatment is discussed in connection with the. intestinal and biliary tract. Bouveret's syndrome is analyzed, including its clinical appearence and the possibility of integral surgical treatment. There is also a chapter that deals with biliobiliary fistulas, analyzing surgical difficulties and suggesting safety procedures for biliary canalization. The complex problem of fistulas of ulcerous orlgin is analyzed and surgical solutions which leave the ulcer and abnormal communication are defended by reáson of their good tollerance.